Reveal a School Branding Model Based on Pesantren - Angga, Angga (JIEM (Journal of Islamic Education Management), 2020)
This paper aims to reveal a school branding model based on Pesantren in SMA Nurul Jadid Paiton Probolinggo. This research uses a qualitative approach with a type of case study. SMA Nurul Jadid Paiton Probolinggo is one of the formal schools based on pesantren which applies Branding Image in enhancing its image. The results of the research on the Branding Image model which is applied in Islamic boarding school-based schools Nurul Jadid Paiton Probolinggo are through 4 main things which include; marketing communication (marketing commonication), consumption experiences, social influences and figures and charisma of kyai.